Protein protection treatments against rumen degradation - Haro Haro, Andres; Picón Saavedra, Marco; José Andrade, María; Bautista, Hugo; Vintimilla, Andrea (EASI: Engineering and Applied Sciences in Industry, 2023)
Ruminant animals may exhibit low nitrogen utilization efficiency due to ammonia losses in the rumen. Moving the site of protein digestion from the rumen to the small intestine can enhance nitrogen efficiency. Therefore, protecting the protein from ruminal degradation through physical or chemical treatments is imperative. The objective of this review was to determine the commonly used protein protection treatments such as the application of physical and chemical methods. Physical, chemical treatments or their combination are justified by the application of feed sources with high-protein value and rapid degradability, to increase the usable protein fraction in the intestine by reducing its rumen degradability.